DISAIN SISTEM PENTANAHAN PROTEKSI PETIR SISTEM MULTIPLE VERTICAL ELECTRODES PADA TERMINAL LAWE-LAWE – PERTAMINA DHP - Redaksi Tim Jurnal (Sutet, 2017)
The purpose of Grounding system design is to ensure safety for personal and equipment, andto improve fault detection of protection system.All electrical equipment should be connected to the grounding system. A system ground refers tothe point in an electrical circuit that is connected to earth. This connection point is typically at theelectrical neutral.Grounding of electrical items must be performed inside the enclosure i.e. insulated copperconductor is going to be used for earthed loop.Grounding bar of equipment, cubicle, switchboard, dedicated inside terminal boxes, lightingfittings.Lightning protection, electrical and instrument equipment should be connected to the groundingsystem separately. The objectives of lightning protection are to avoid catastrophic equipment damage and to preventpersonal injury. The energy of a lightning stroke can readily ignite flammable vapors or damageequipment.Methode of calculation used of the groundingsystem design of lightning protection is multiple vertical electrodes system.